The Role of Home Industry in Improving Family Welfare of Tofu Home Industry Employees According to Islamic Economics in Aek Lancat Village, Lubuk Barumun District - Junda Harahap; Nur Hakima Akhirani Nasution; Rini Angraeni (PT Inovasi Pratama Internasional, 2023)
The purpose of this study was to determine the role of the tofu home industry in Aek Lancat Village in improving the welfare of employees' families . To find out how the role of the home industry in improving the welfare of the families of employees in Aek Lancat Village according to Islamic Economics. Home industry is a business activity that is able to expand employment and provide broad economic services to the community, reduce unemployment and improve people's welfare. This type of research is field research (field research) which is obtained through a reference center by going directly to the field (research site ) to view and retrieve data directly. The data sources for workers in the tofu home industry in Aek Lancat Village are Kholijah Hasibuan and Midar Hasibuan, besides that there are several buyers from local residents such as Mrs. Seftiani, as well as small traders around the village of Aek Lancat. An increasingly efficient industrial sector in a national economy requires small companies in the management industry. The growth of home industries in rural areas will improve the village economy with various types of business activities and community skills. Tofu home industry in Aek Lancat Village, Kec. Lubuk Barumun in its business activities can help build the local community's economy because this business is related to livelihoods. Home industry y This is very helpful in building the community's economy, especially in the family economy.